Plastic-degrading clusters of orthologous groups reveal near-universal biodegradation potential in prokaryotes - Mustari, Shakira; Phạm, Loan Tú; Saikkonen, Kari; Nakamura, Miho; Puigbò, Pere (Elsevier, 2026)
Micro- and nanoplastic pollution (MNPP) is an increasing environmental threat due to the persistence, dispersal, and potential toxicity of plastic particles. Although microbial biodegradation offers a sustainable mitigation strategy, a comprehensive understanding of plastic-degrading proteins across microbial taxa is lacking. Here, we present the Plastic-Degrading Clusters of Orthologous Groups (PDCOGs) database (https://phylobone.com/microworld/PDCOG), comprising 625,616 potential plastic-degrading proteins (PPDPs) from free-living prokaryotes organized into 51 orthologous groups. The database/PDCOGs enable systematic analysis of microbial plastic-degrading capacity across ecosystems and phylogenetic lineages. Notably, PPDPs constitute ∼3.5% of all prokaryotic proteins, with over 95% of the species having the potential to biodegrade at least one plastic polymer type. This resource provides a genomic tool/framework for exploring the ecological and evolutionary importance of plastic biodegradation and supports future efforts to mitigate the global MNPP crisis.